2015
DOI: 10.1016/j.physletb.2015.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Power law Starobinsky model of inflation from no-scale SUGRA

Abstract: We consider a power law $\frac{1}{M^2}R^{\beta}$ correction to Einstein gravity as a model of inflation. The interesting feature of this form of generalization is that small deviations from the Starobinsky limit $\beta=2$ can change the value of tensor to scalar ratio from $r \sim \mathcal{O}(10^{-3})$ to $r\sim \mathcal{O}(0.1)$. We find that in order to get large tensor perturbation $r\approx 0.1$ as indicated by BKP measurements, we require the value of $\beta \approx 1.83$ thereby breaking global Weyl symm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 90 publications
(118 reference statements)
4
19
0
Order By: Relevance
“…[1] as well as to (b) aµ 4 (R/µ 2 ) 2−b . Inflation built based on the former form was also studied in [38,40,43], while on the latter formin [36,[44][45][46]. One should point out however, that for any finite b these models are not equivalent to (3).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] as well as to (b) aµ 4 (R/µ 2 ) 2−b . Inflation built based on the former form was also studied in [38,40,43], while on the latter formin [36,[44][45][46]. One should point out however, that for any finite b these models are not equivalent to (3).…”
Section: The Modelmentioning
confidence: 99%
“…where t e denotes the time at the end of inflation (at which E = 1), and φ Ee = φ E (t e ), When taken together, and these two sets of (parametric) relations tell us how n s , r and α depend on N . Unfortunately, the form of the effective potential (35) is rather complicated such that we were unable to perform the integral (44). Nevertheless, with a help of the symbolic package Mathematica, we were able to plot the relevant curves.…”
Section: B Cosmological Perturbations In Our Modelmentioning
confidence: 99%
“…For example, considering the f (R) gravity, with f (R) = R + a R n , we have found that IceCube data and DM relic abundance can be explained provided n < 1, However, such a value is not favored by recent Planck release, which require n > 1 (and in fact the Starobisnky model n = 2 is one of the favorite candidate for Inflation) [114,115]. Results here discussed do not allow to distinguish between f (T ) and BD theories of gravity.…”
Section: Discussionmentioning
confidence: 98%
“…We now study a model R + 2 and so we call it as power law Starobinsky model [99]. M and β are the two dimensionless parameters.…”
Section: The Power Law Model R + R βmentioning
confidence: 99%